Zr‐Metal Organic Framework and Derivatives for Adsorptive and Photocatalytic Removal of Acid Dyes: Lin et al. (1st February 2018) - Lin, Kun‐Yi Andrew; Yang, Hongta; Hsu, Fu‐Kong
ABSTRACT: : To investigate effects of modification of MOFs on removal of acid dyes via adsorption and photodegradation, zirconium‐based MOF, UiO‐66, and its derivatives were synthesized. UiO‐66 derivatives were prepared by using amine (NH2 )‐containing ligand and incorporating carbon nanotubes (CNTs) and reduced graphene oxide (RGO). During the synthesis UiO‐66‐NH2, UiO‐66‐CNT and UiO‐66‐RGO, were obtained, respectively. While UiO‐66‐NH2 showed the enhanced adsorption capacity for acid dyes owing to the electrostatic attraction, CNTs were found to be the most effective addition to enhance the adsorption of acid dyes. However, the addition of RGO in UiO‐66 (to form UiO‐66‐RGO) exhibited the highest removal efficiency via photodegradation compared to UiO‐66 and other derivatives probably attributed to its unique layered morphology. The presence of NH2, CNTs and RGO not only significantly improved the adsorption capacity for acid dyes but also enabled these UiO‐66 derivatives to exhibit photocatalytic activity under visible light irradiation.